Careful science? Bodywork and care practices in randomised clinical trials. Issue 5 (6th November 2013) - Jespersen, Astrid P.; Bønnelycke, Julie; Eriksen, Hanne H.
Abstract Concern about obesity has prompted numerous public health campaigns that urge people to be more physically active. The campaigns often include normative statements and attempt to impose restrictions on individuals' lives without considering the complexities of daily life. We suggest that broadening the focus to reflect everyday practices would foster better targeted public health campaigns. This article is based on our participation in FINE, a multidisciplinary Danish research project. The core methodology of FINE was a randomised controlled trial in which 61 moderately overweight men were put into different exercise groups. In this article we analyse the scientific work of the trial as representing entangled processes of bodywork, where data are extracted and objectified bodies are manipulated and care practices address the emotional, social and mundane aspects of the participants' everyday lives. Care practices are an inherent part of producing scientific facts but they are removed from the recognised results of scientific practice and thus from common public health recommendations. However, knowledge about the strategic use of care practices in lifestyle interventions is important for public health initiatives and future efforts should incorporate this aspect.